2000
DOI: 10.1086/315450
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hepatitis C Virus–Specific CD8+T Cells with Viral Clearance in Acute Hepatitis C

Abstract: CD8+ T lymphocytes play a major role in antiviral immune defense. Their significance for acute hepatitis C is unclear. Our aim was to correlate the CD8+ T cell response with the outcome of infection. Eighteen patients with acute hepatitis C and 19 normal donors were studied. Hepatitis C virus (HCV)-specific CD8+ T cells were identified in the enzyme-linked immunospot assay by their interferon-gamma (IFN-gamma) production after specific stimulation. The highest numbers of IFN-gamma-producing HCV-specific CD8+ T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
239
1
6

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 345 publications
(258 citation statements)
references
References 24 publications
11
239
1
6
Order By: Relevance
“…It is characterised by a high tendency to chronicity, which often progresses to cirrhosis and liver cancer [2]. Viral clearance after acute hepatitis or after IFN-␣ therapy is usually associated with strong CD4 and CD8 T cell responses [3][4][5][6][7][8][9][10][11][12]. In particular, cellular T helper immune response against nonstructural NS3 HCV protein has been associated with viral clearance after acute infection, whereas absence of this Tcell response leads to viral persistence and chronic hepatitis [9,13].…”
Section: Introductionmentioning
confidence: 99%
“…It is characterised by a high tendency to chronicity, which often progresses to cirrhosis and liver cancer [2]. Viral clearance after acute hepatitis or after IFN-␣ therapy is usually associated with strong CD4 and CD8 T cell responses [3][4][5][6][7][8][9][10][11][12]. In particular, cellular T helper immune response against nonstructural NS3 HCV protein has been associated with viral clearance after acute infection, whereas absence of this Tcell response leads to viral persistence and chronic hepatitis [9,13].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, patients who spontaneously recover from HCV infection typically mount vigorous HCV-specific CD4 + and CD8 + T cell responses that are directed against multiple viral peptides and are readily detectable in the blood (5)(6)(7)(8)(9). By contrast, patients with chronic hepatitis C tend to have late, transient, and/or narrowly focused T cell responses (9,10).…”
mentioning
confidence: 99%
“…Natural history studies have found that 15%-59% of people who are infected with HCV will undergo spontaneous viral clearance with no further liver disease due to HCV [3][4][5][6][7][8][9][10][11] . The remaining will develop chronic HCV infection that can lead to cirrhosis, hepatocellular carcinoma and the need for a liver transplant.The exact mechanism of HCV RNA clearance is not well understood although recent studies have shown that clearance is associated with strong, broad cellular immune responses [12][13][14][15][16][17][18][19] . Other factors such as younger age [3,20] , female gender [21,22] , presence of hepatitis B surface antigen (HBsAg) [3,23] , certain HLA alleles [6,[24][25][26][27][28][29] , and low viral quasispecies diversity [30] have been linked to increased HCV RNA clearance.…”
mentioning
confidence: 99%